Optimalisasi Pemilihan Driver Menggunakan Algoritma Simple Additive Weighting (SAW) Pada Aplikasi XYZ - Razitul Ikhlas; Yuhefizar; Ervan Asri (Ikatan Ahli Informatika Indonesia, 2021)
Decision Support System (DSS) is built to facilitate an agency or company in making a decision, as is the case in the selection of drivers in the XYZ application. In the selection of drivers, quick and precise decisions are needed by considering the criteria that have been set. One of the algorithms that can be used to make a decision is the simple additive weighting (SAW) algorithm. The simple additive weighting (SAW) algorithm is applied in the driver selection process for the XYZ application. By entering several weighted value criteria such as distance, driver rating, and total driver order. After applying this algorithm, the driver search results are more optimal than before.